Evaluation of hydrological components using swat hydrological model for poko river basin - Nguyen , Thi Tinh Au (Journal of Technical Education Science, 2020)
In this study, Poko river basin is selected for evaluation of water resources in the basin, as there is a decline inflow due to reduced rainfall over years and also due to increased activities in the upstream areas of the catchment. The study focused on evaluation of hydrological components for Poko river basin using hydrological model known as soil and water assessment tool (SWAT). The model was implemented for Poko river basin using digital elevation model (DEM), land use, soil and meteorological data etc. The model performance was evaluated by calibration and validation approach. The model was first calibrated for the period from 2000 to 2005 and then validated for the period from 2006 to 2018 using the observed stream flow data from Dak Mot stream gauge within the watershed. It is found that the coefficient of determination (R²) and Nash- Sutcliffe index (NSI), and Percent BIAS (PBIAS) during the calibration process was 0.81, 0.64 and 12.1 respectively and validation process was 0.74, 0.60 and 13.5 respectively. All coefficients are satisfying the model results and are used for evaluating the hydrological components for the basin. Finally, the values were evaluated for Poko river basin for different hydrological components like water yield, evapotranspiration, groundwater recharge, sediment yield and discharge. The results can be used for decision making purpose and further for the planning of water harvesting plan.